(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This article discusses common joint diseases in the human body (arthritis, arthrosis, and rheumatoid arthritis) and explains the role of medicinal plants in managing these conditions. It outlines how joint disorders may be addressed with herbal remedies in home settings and which herbs are traditionally used for this purpose. In particular, it highlights the composition, pharmacological effects, and beneficial properties supported by clinical research for plants widely used in folk medicine, such as ginger, cinnamon, licorice, fennel, and radish.